Cinnamic Acid and Sorbic acid Conversion Are Mediated by the Same Transcriptional Regulator in Aspergillus niger - Lubbers, Ronnie J. M.; Dilokpimol, Adiphol; Navarro, Jorge; Peng, Mao; Wang, Mei; Lipzen, Anna; Ng, Vivian; Grigoriev, Igor V.; Visser, Jaap; Hildén, Kristiina S.; de Vries, Ronald P. (Frontiers in Bioengineering and Biotechnology, 2019)
Cinnamic acid is an aromatic compound commonly found in plants and functions as a central intermediate in lignin synthesis. Filamentous fungi are able to degrade cinnamic acid through multiple metabolic pathways. One of the best studied pathways is the non-oxidative decarboxylation of cinnamic acid to styrene. In Aspergillus niger, the enzymes cinnamic acid decarboxylase (CdcA, formally ferulic acid decarboxylase) and the flavin prenyltransferase (PadA) catalyze together the non-oxidative decarboxylation of cinnamic acid and sorbic acid. The corresponding genes, cdcA and padA, are clustered in the genome together with a putative transcription factor previously named sorbic acid decarboxylase regulator (SdrA). While SdrA was predicted to be involved in the regulation of the non-oxidative decarboxylation of cinnamic acid and sorbic acid, this was never functionally analyzed. In this study, A. niger deletion mutants of sdrA, cdcA and padA were made to further investigate the role of SdrA in cinnamic acid metabolism. Phenotypic analysis revealed that cdcA, sdrA and padA are exclusively involved in the degradation of cinnamic acid and sorbic acid and not required for other related aromatic compounds. Whole genome transcriptome analysis of ΔsdrA grown on different cinnamic acid related compounds, revealed additional target genes, which were also clustered with cdcA, sdrA and padA in the A. niger genome. Synteny analysis using 30 Aspergillus genomes demonstrated a conserved cinnamic acid decarboxylation gene cluster in most Aspergilli of the Nigri clade. Aspergilli lacking certain genes in the cluster were unable to grow on cinnamic acid, but could still grow on related aromatic compounds, confirming the specific role of these three genes for cinnamic acid metabolism of A. niger.